Electrodynamics of molecular organic superconductors studied by mu SR - Pratt, F; Blundell, S; Lancaster, T; Lee, S; Toyota, N (2004)
The response of the superconducting charge carriers to an applied magnetic field has been probed in a number of organic superconductors using muSR. Systematic studies have been made of the in-plane superconducting penetration depth lambda in superconductors based on the ET and BETS molecules. These studies have revealed a strong correlation between lambda and T-c. This type of correlation was first noted in high T-c cuprates by Uemura et al who found a linear relation between T-c and lambda(-2). In the case of organic superconductors, however, we find that the overall con-elation is better described as T-c proportional to lambda(-3). Understanding this characteristic trend should provide some important clues about the nature of the superconductivity in the organic superconductors; several possible models are considered here for describing this behaviour. It is concluded that models in which the superconducting carrier concentration is tied to the nominal band filling are inconsistent with the observed scaling behaviour.